2012
DOI: 10.1155/2012/742162
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Model for Cavitational Flow in Hydraulic Poppet Valves

Abstract: The paper presents a numerical simulation and analysis of the flow inside a poppet valve. First, the single-phase (liquid) flow is investigated, and an original model is introduced for quantitatively describing the vortex flow. Since an atmospheric outlet pressure produces large negative absolute pressure regions, a two-phase (cavitating) flow analysis is also performed. Both pressure and density distributions inside the cavity are presented, and a comparison with the liquid flow results is performed. It is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Exemplary results of visualization studies of the working medium flow through the orifice of the overflow valve and results of the measurement of the accompanying acoustic effect are reported. Cavitation is indicated as a significant source of noise, which is confirmed by the literature, e.g., [6]. The experimental studies were carried out on original test stands, which are presented in this paper.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Exemplary results of visualization studies of the working medium flow through the orifice of the overflow valve and results of the measurement of the accompanying acoustic effect are reported. Cavitation is indicated as a significant source of noise, which is confirmed by the literature, e.g., [6]. The experimental studies were carried out on original test stands, which are presented in this paper.…”
Section: Introductionsupporting
confidence: 62%
“…This is sometimes achieved through the use of vibration isolators on which hydraulic valves can be mounted to minimize the transfer of vibrations to the valve housing, and so to the control element [5]. Another cause of the vibration of the overflow valve head is the implosion of vapour bubbles, which contributes to noise intensification [6]. In [7] a r c h i v e s o f c i v i l a n d m e c h a n i c a l e n g i n e e r i n g x x x ( 2 0 1 5 ) x x x -x x x a r t i c l e i n f o Article history: the author states, on the basis of the cited literature, that the instability of the overflow valve head is due to: (a) the coupled motions of the head and other system components, (b) the transition of the laminar flow to the turbulent flow, accompanied by an increase or decrease in head displacement, (c) the negative flow restoring force, (d) the pressure difference between valve opening and closing and (e) the fluctuation of supply pressure.…”
Section: Introductionmentioning
confidence: 99%
“…From the 90's, with the development of computational methods, the computational analysis of the complex flows through valves have became more feasible thus leading to substantial research into the operation and design of SRVs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For example, Vu and Wang [1] investigated the complex three-dimensional flow field of an oxygen SRV during an incident with CFD (computational fluid dynamics) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown the value of CFD when determining the effects of water hammer in pipes [8]. Further, CFD have been used successfully to model cavitation and the risk of cavitation erosion in diesel injectors [9,10] and hydraulic valves [11,12]. However, the cavitation in these studies is a consequence of the accelerated flow and cavitation as the result of hydraulic transients has not been considered.…”
Section: Introductionmentioning
confidence: 99%